2020
DOI: 10.1002/hpja.391
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring what it means to be healthy for young Indigenous Australians and the role of social media in influencing health behaviour

Abstract: Indigenous health outcomes are sought after by governments and communities as a priority. 1,2 In Australia, existing evidence suggests strategies to improve the health of Aboriginal and Torres Strait Islander (hereafter referred to as Indigenous) people must address underlying determinants of health. 3 This includes conceptualising health as biopsychosocial, spiritual and cultural wellbeing, being culturally safe 4 and being led by -or in partnership with and providing back to -the community. 4,5 Yet, a gap re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Some literature reviews were also included, as well as grey literature ( n = 3; 2.7%) [ 39 , 40 , 41 ]. For empirical studies, the study populations ranged from n = 18 [ 42 ] to n = 33,097 [ 43 ] and included a range of ages from 13 to 69. Whilst the research question focused on EAs aged 18–25, results identified multiple definitions of the age range for EAs, as well as studies that intersected or included the 18–25 age group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature reviews were also included, as well as grey literature ( n = 3; 2.7%) [ 39 , 40 , 41 ]. For empirical studies, the study populations ranged from n = 18 [ 42 ] to n = 33,097 [ 43 ] and included a range of ages from 13 to 69. Whilst the research question focused on EAs aged 18–25, results identified multiple definitions of the age range for EAs, as well as studies that intersected or included the 18–25 age group.…”
Section: Resultsmentioning
confidence: 99%
“…Uijtdewilligen et al [ 75 ] hinted at cultural differences in the research population but did not study cultural influences directly. Conversely, Walker et al’s study into the health of Indigenous Australian EAs took a direct approach at understanding the cultural influences that impacted Indigenous Australians’ health [ 42 ]. There is further opportunity to explore the role that cultural norms continue to play in EAs’ behaviours, especially through the shift between parental/family and peer influences during this life stage.…”
Section: Discussionmentioning
confidence: 99%
“…The studies took place across all Australian states and territories, with six studies taking place across multiple states and territories [ 29 , 30 , 31 , 33 , 40 , 41 ]. Eight took place solely in Queensland (Qld) [ 32 , 36 , 42 , 43 , 44 , 45 , 46 , 47 ], two in Victoria [ 38 , 48 ], two in New South Wales (NSW) [ 49 , 50 ], three in the Northern Territory (NT) [ 18 , 35 , 51 ], three in Western Australia (WA) [ 34 , 37 , 52 ], one in South Australia (SA) [ 39 ], and one in Tasmania (Tas) [ 53 ]. One study did not report a location [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study did not report a location [ 54 ]. Nine studies took place in multiple geographic contexts [ 29 , 30 , 31 , 33 , 37 , 40 , 41 , 48 , 50 ]. Nine took place solely in urban settings [ 32 , 34 , 38 , 39 , 42 , 44 , 45 , 49 , 53 ], two in rural/regional settings [ 46 , 47 ] and seven in remote settings [ 18 , 35 , 36 , 43 , 51 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation